Temperature-Dependent Performance of Organic Light-Emitting Devices based on Solution-Processed N,N′-Bis-(1-Naphthyl)-N,N′-Diphenyl-1,1′-Biphenyl-4,4′-Diamine Hole Transport Layers - Nguyen, Huu Tuan; Duong, Anh Tuan; Nguyen, Tuan Hong; Lee, Soonil (Journal of Electronic Materials, 2023)
A series of green organic light-emitting diodes (OLEDs) that consisted of a tris-(8-hydroxyquinoline)aluminum emitting layer and an N,N′-bis-(1-naphthyl)-N,N′-diphenyl-1,1′-biphenyl-4,4′-diamine (NPB) hole transport layer were fabricated and characterized. The NPB layers were formed using a solution process and heated at different temperatures. All the fabricated OLEDs showed similar electroluminescence spectra: however, different heat treatment temperatures resulted in efficiency variations. The peak luminous efficiency revealed a significant increase by ~70% when the temperature was increased from 80°C to 100°C and a dramatic decrease by ~57% after a further increase in temperature to 110°C. As a result, the best performance was observed from the device with a treatment temperature of 100°C; the maximum luminance and luminous efficiency were 7600 cd/m2 and 2.75 cd/A, respectively. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Hole transport layers; Lightemitting diode; Luminous efficiency; NPB HTL; Organic light-emitting; Organic light-emitting devices; Organic light-emitting diode; Performance; Temperature dependence; Temperature dependent; NPB HTL; OLEDs; spin-coating; temperature dependence